Boundary element analysis of laminated composite shear deformable shallow shells. (1st September 2018) - Useche, J.; Medina, C.
Abstract: In this work, a Boundary Element Method formulation for stress analysis of symmetrically laminated composite thick shallow shells is presented. The proposed formulation was obtained by coupling the boundary element formulation of shear deformable symmetrically laminated composite plates and the boundary element formulation for two-dimensional anisotropic plane stress analysis. Formulation uses the elastostatic anisotropic fundamental solutions proposed for these formulations. Domain integrals are transformed to the boundary by using the Radial Integration Method. Numerical examples are presented to demonstrate the efficiency and accuracy of the formulation. Obtained results concur with results available in the literature as well as with finite element results.